2016
DOI: 10.2307/j.ctvb4bsnt
|View full text |Cite
|
Sign up to set email alerts
|

Female Piety and the Invention of American Puritanism

Abstract: Jenny Franchot did not live even to see this book begin, but her intellectual spirit is the driving force behind it. Thanks, Jenny.There was a time not too long ago when it looked like this book would never be more than an infrequently accessed folder on a desktop. It was at all times, during those difficult years, a frequently accessed source of self-pity. So I would like to thank the friends of Bill W. for seven years of teaching me about humility, accountability, and the importance of helping others. The la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Bryce Traister has observed that Wigglesworth's "sexual life authenticates and makes possible the drama of his own salvific narrative." 46 Indeed, Wigglesworth's recording of his sexual life pushes his private salvific narrative into a region unauthorized by what we would assume are viable models of a puritan's public piety. torment of "carnal concupiscence" and "lust" make him finally admit to himself that "marriage wil be necessary," he marries on May 18, 1655.…”
Section: Queer Sacramental Temporality In Michael Wigglesworthmentioning
confidence: 96%
“…Bryce Traister has observed that Wigglesworth's "sexual life authenticates and makes possible the drama of his own salvific narrative." 46 Indeed, Wigglesworth's recording of his sexual life pushes his private salvific narrative into a region unauthorized by what we would assume are viable models of a puritan's public piety. torment of "carnal concupiscence" and "lust" make him finally admit to himself that "marriage wil be necessary," he marries on May 18, 1655.…”
Section: Queer Sacramental Temporality In Michael Wigglesworthmentioning
confidence: 96%
“…Scholars of early American literature provide the most trenchant critiques thus far of the secularization thesis. Bryce Traister observes the ways in which piety and secularism were intertwined from the seventeenth century forward. Sarah Rivett shows how empiricism enabled a new discourse of religious inquiry in colonial New England: “Grace…came to be conceived of as having a traceable, mappable nature that, were it to be identified upon human souls, could be treated as empirical evidence” (46).…”
Section: Postsecularism and Eighteenth‐century Literary Studiesmentioning
confidence: 99%